Evapotranspiration of tomato simulated with the CRITERIA model - Pasquale Campi; Francesca Modugno; Marcello Mastrorilli; Fausto Tomei; Giulia Villani; Vittorio Marletto (Italian Journal of Agronomy)
The CRITERIA model simulates crop development and water dynamics in agricultural soils at different spatial scales. The objective of this paper was to test CRITERIA in order to evaluate the suitability of the model as a tool for scheduling irrigation at field scale. The first step of the work was to validate this hypothesis, by means of calibration and validation of CRITERIA on processing tomato in two experimental sites in Southern Italy (Rutigliano and Foggia) for the years 2007 and 2008 under different irrigation regimes. The irrigation treatments were: i) absence of plant water stress (the control treatments set up for both years and sites), ii) moderately stressed (applied in Rutigliano for 2007), and iii) severely stressed (applied in Foggia for 2008). The second step consisted in the evaluation of the expected impact of different irrigation regimes on daily actual evapotranspiration. For model calibration, the 2007 data of the control treatment was used, whereas in the validation process of actual evapotranspiration, the other part of the dataset was used. The observed data were crop evapotranspiration, agrometeorological data, leaf area index, physical-chemical and hydrological characteristics of soil, phenological stages and irrigation management. In order to evaluate model performance we used three statistical indicators to compare simulated and measured values of actual evapotranspiration: the normalized differences of seasonal values are less than 10% for all treatments; the model efficiency index on the typical period between two irrigations (4 days) was positive for all treatments, with the best values in the Foggia site, for both the irrigated and the severely stressed experiments; the relative root mean square error (RRMSE) was smaller than 20% in both the control treatments, but higher than 30% for the stressed treatments. The increase in RRMSE for the stressed experiments is due to CRITERIA simulating a crop in good soil water conditions and, as a consequence, with a larger evapotranspiration demand with respect to water stressed crop. Therefore, we can consider CRITERIA as a suitable tool to manage irrigations of processed tomato, especially for the full irrigation regime; an improvement can be reached by simulating the impact of water stress conditions on the eco-physiological parameters of the crop, in order to use the model also under deficit irrigation regimes.